PENGARUH KEPUASAN, HAMBATAN BERPINDAH DAN PENYEDIAAN FASILITAS TERHADAP LOYALITAS KONSUMEN DI HOTEL NOVOTEL SURABAYA - Yenny Chen Sutjiawan (Jurnal Strategi Pemasaran, 2014)
The aim of this study was to determine the effect of satisfaction , switching barriers and voice to customer loyalty at Hotel Novotel Surabaya, as well as knowing the dominant effect between variables of satisfaction, switching barriers and voice to customer loyalty at Hotel Novotel SurabayaThis type of research is the use of causal. The population in this study is the consumer who stayed 1 last year and resides in Surabaya . The sampling technique used was a convenience sampling with sample characteristics are those who visit and stay at Hotel Novotel . The analysis technique used is multiple linear regression analysis to test the hypothesis using the F test and t test .The results showed that satisfaction, switching barriers and complaint handling affect is simultan and partial to customer loyalty Novotel hotels in Surabaya, as well as voice of customer variable dominant influence on the loyalty shown by the value of t ( 6.209 ) is the largest compared to the variable another ( satisfaction = 4.638 and voice of customer = 3.361).